The impact of the 2020 diagnostic reference level revision and the development of national regulations on occupational radiation protection in medical facilities in Japan - Tsujiguchi, Takakiyo; Ishikawa, Taito; Arakida, Satoshi; Kanozawa, Taiga; Suzuki, Teru; Sakamoto, Hajime; Sasaki, Takeshi; Narita, Masataka; Takahashi, Yasuyuki (Frontiers in Public Health, 2025)
This study examined the impact of revisions to the diagnostic reference levels and the Regulation on Prevention of Ionizing Radiation Hazards on radiation safety management in medical institutions by investigating changes in the awareness of occupational and medical radiation exposure and improvements in radiation protection. A self-administered questionnaire was sent to 799 facilities with angiography or nuclear medicine departments and responses were obtained from 424 facilities. The results showed that nonuniform exposure assessments were conducted in 93% of the facilities. Following regulatory revision, protective measures were reassessed in many facilities, leading to the increased use of protective eyewear and lens dosimeters. Notably, the adoption rate of lens dosimeters reached approximately 60%, suggesting heightened concerns about lens exposure. After the publication of the 2020 Diagnostic Reference Levels, many medical institutions reviewed the exposure conditions, with approximately 90% of the CT facilities modifying their parameters. These findings indicate that regulatory changes have contributed to an increased awareness of radiation protection and the reinforcement of specific protective measures.